The Impact Of Omnichannel Retail On Customer Patronage Intentions: The Role Of Consumer Empowerment, Service Failure, And Customer Satisfaction - Aldino Putra Pambudi; Yolanda Masnita; Kurniawati Kurniawati (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
The effects of omnichannel integration on customers are examined in this study along with the mediating roles that customer empowerment, customer satisfaction, and service failure perform. Omni-channel retail enables order processing convergence through continuous information exchange, general operations, logistics, and operations with inventory across all channels. To gather information, 160 young Indonesian consumers who have utilized omnichannel-based applications will be questioned. In order to verify validity, reliability, and hypothesis testing, the data was processed using SMART PLS. The findings show that omnichannel integration increases consumer empowerment and satisfaction, which has a beneficial impact on purchasing intentions. The customer's intents are positively impacted by the service's failure as well. This study deepens our understanding of how multichannel shopping boosts purchase and patronage intentions by maintaining services across online and physical channels. In addition to the conclusion that customers prefer omnichannel, research on retail literature, customer experience, and e-commerce is demonstrating the ways in which internal consumer states influence consumers' buy intentions.